Altruism in society: Evidence from a natural experiment involving commuters - Redzo Mujcic; Paul Frijters (Institute for the Study of Labor (IZA), 2011)
We study social preferences in the form of altruism using data on 959 interactions between random commuters at selected traffic intersections in the city of Brisbane, Australia. By observing real decisions of individual commuters on whether to stop (give way) for others, we find evidence of (i) gender discrimination by both men and women, with women discriminating relatively more against the same sex than men, and men discriminating in favour of the opposite sex more than women; (ii) status-seeking and envy, with individuals who drive a more luxury motor vehicle having a 0.18 lower probability of receiving a kind treatment from others of low status, however this result improves when the decision maker is also of high status; (iii) strong peer effects, with those commuters accompanied by other passengers being 25 percent more likely to sacrifice for others; and (iv) an age effect, with mature-aged people eliciting a higher degree of altruism.
urn:nbn:de:101:1-201104193357
Keywords: D64; D03; C90; H11; H77; 330; altruism; social interaction; social discrimination; status; peer effects; commuters; Altruismus; Soziale Beziehungen; Diskriminierung; Sozialer Status; Soziale Gruppe; Feldforschung; Pendelverkehr; Brisbane